Mapping Nutrient Status of Phosphate, Soil pH and Organic Carbon of Paddy Fields In Meijan Village Balige District Toba Regency - Kuswandi, Haris; Syawal Harahap, Fitra; Hariyati Adam, Dini; Ayu Putri Septiyani, Ika (International Journal of Science and Environment (IJSE), 2024)
The purpose of this research is to survey and mapping nutrient status of total phosphate, available phosphate, soil pH and organic carbon at paddy fields Meijan Village Balige District Toba Regency and its influence on rice production. Soil samples was analyzed at the Analytical Laboratory of PT Socfindo Indonesia North Sumatera Province. Which began in October to December 2023 The method used is Free Grid Survey semidetailed level survey and analysis of nutrient data total phospate by Acid destruction method (HClO4), available phosphate by Bray II method, soil pH by H2O extraction and organic carbon by walkley & black method and then interpret to the map nutrient status. The result of research showing that status total phosphate classified by 3 status such as, medium (81,59 ha), high (81,15 ha) and very high (27,26 ha). Available phosphate classified in 3 nutrient status such as very low (39,11 ha), low (137,40 ha) and medium (13,49 ha). Soil pH classified in 2 status such as moderately acidic (30,16 ha) and strongly acidic (159,84 ha). Organic carbon classified by 3 nutrient status such as very low (3,06 ha), low (135,84 ha) and medium (51,10 ha). Available phosphate and organik carbon affect rice production in Meijan Village Balige District Toba Regency.